Innovative Robot Designs and Approaches - Carbone, Giuseppe; Laribi, Med Amine (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to disseminate the latest research achievements, findings, and ideas in the robotics field, with particular focus on the Italian scenario. It covers a range of topics related to the theory, design, practice, and applications of robots, such as robot design and kinematics, dynamics of robots and multi-body systems, linkages and manipulators, control of robotic systems, trajectory planning and optimization, innovative robots and applications, industrial robotics, collaborative robotics, medical robotics, assistive robotics, and service robotics. The reprints contributions include (but are not limited to) revised and substantially extended versions of selected papers that were presented at the 2nd International Conference of IFToMM, Italy (IFIT 2018).